Meluruskan Logika Pemerintah Soal Kegentingan Moratorium UU Kepailitan dan PKPU - Serlika Aprita (ADALAH, 2022)
The discussion that emerged from the moratorium on the Bankruptcy Law and the PKPU, all forms of changes to regulations are the absolute right of the Government which of course, before issuing the policy, the Government has considered and reviewed all inputs from stakeholders. As the main purpose of the decision is in the public interest. the concept of PKPU and bankruptcy only by considering the indications of “Moral Hazard” that may arise in the process. The spirit of business continuity adopted by the Bankruptcy Law and PKPU must be taken into consideration because it has been proven to have saved several debtors from business destruction. The imposition of a moratorium is not the only way out to avoid the threat of "Moral Hazard" which can actually be handled by other mechanisms. The solution or input that can be considered by the Government is to encourage changes, improvements, and improvements in the Bankruptcy Law and PKPU, either through the Perppu mechanism or other mechanisms. Changes or improvements will be good if they go into a more substantial or basic real.